1987
DOI: 10.1111/j.1365-2044.1987.tb05313.x
|View full text |Cite
|
Sign up to set email alerts
|

Nalbuphine for obstetric analgesia

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…These findings contradict other published results showing greater pain relief after the administration of nalbuphine than of pethidine [6,7]. Our results are however consis tent with a recent prospective study of intramuscular administration of nalbuphine and pethidine during labor [3].…”
Section: Discussioncontrasting
confidence: 57%
“…These findings contradict other published results showing greater pain relief after the administration of nalbuphine than of pethidine [6,7]. Our results are however consis tent with a recent prospective study of intramuscular administration of nalbuphine and pethidine during labor [3].…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, even where all women appeared to be accounted for at follow-up, there were frequently missing data for specific outcomes. In some studies loss to follow-up or missing data were greater than 10% (Bitsch 1980; Fairlie 1999; Hamann 1972; Levy 1971; Moore 1970; Mowat 1970; Olson 1964; Wilson 1986), or greater than 20% (De Boer 1987; Frank 1987; Giannina 1995; Gillam 1958; Nicholas 1982; O’Dwyer 1971; Refstad 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also reported that there is no meaningful difference in infants' Apgar score. 12,14,16 We were not able to determine the reason for the difference in infant Apgar scores for the first minute between the two groups.…”
Section: Discussionmentioning
confidence: 97%
“…There was no significant difference in blood pressure, heart rate and respiratory rate in the mothers before and after injection (p>0.05), and there was also no significant difference in fetal heart rate before and after injection (p>0.05). In a study by Frank et al (1987) that evaluated the side effects of pethidine on mother and infant, blood pressure, heart rate and respiratory rate in mothers and fetal heart rate and Apgar score in infants were controlled. They concluded that the administration of 75 mg pethidine has no side effects on the mother or her fetus.…”
Section: Discussionmentioning
confidence: 99%